ESTIMATION OF SERUM HOMOCYSTEINE LEVEL IN WOMEN WITH POLYCYSTIC OVARIAN SYNDROME (PCOS) - A CASE CONTROL STUDY. - V.S. KALAI SELVI,; K.PRABHU,; E.SIVARAM, (International Journal of Pharma and Bio Sciences, 2015)
Polycystic ovarian syndrome (PCOS) is one of the common endocrine conditions roughly affecting about 6-10% women of reproductive age. It is characterized by ovarian dysfunction, hirsuitism, hyperandrogenism, insulin resistance and obesity. Homocysteine is a sulphur containing amino acid formed during the metabolism of methionine. It has cytotoxic effects on vascular endothelium. Hyperhomocystinemia contribute to the development of cardiovascular disease as evidenced by many studies. Women with PCOS are likely to develop components of metabolic syndrome, such as disturbance of carbohydrate metabolism, obesity, hypertension and dyslipidemia, which in turn are risk factors for cardiovascular disease (CVD), since there is a strong association between serum homocysteine levels and insulin resistance. With this background, this study focuses the level of homocysteine in PCOS patients and to compare the same in normal healthy women. This study is a Case Control Study conducted in Sree Balaji Medical College and Hospital. Fifty women of reproductive age were included in this study, comprising of 25 PCOS women and 25 women without PCOS. The serum homocysteine level was measured using GenX homocysteine enzymatic method (Proton) in fully automated analyzer. Mean level of homocysteine in PCOS was 10μmol/l and non-PCOS was 4μmol/l. The p-value of 0.01 was taken statistically significant. Homocysteine level was found to be elevated in women with PCOS when compared to the women without PCOS.